Antiretroviral drug class and anaemia risk in the current treatment era among people living with HIV in the USA: a clinical cohort study. Issue 3 (19th March 2020) - Harding, Barbara N; Whitney, Bridget M; Nance, Robin M; Crane, Heidi M; Burkholder, Greer; Moore, Richard D; Mathews, W Christopher; Eron, Joseph J; Hunt, Peter W; Volberding, Paul; Rodriguez, Benigno; Mayer, Kenneth; et al.
Abstract : Objective: Anaemia is common among people living with HIV (PLWH) and has been associated with certain, often older, antiretroviral medications. Information on current antiretroviral therapy (ART) and anaemia is limited. The objective was to compare the associations between anaemia incidence or haemoglobin change with core ART classes in the current ART era. Design: Retrospective cohort study. Setting: USA-based prospective clinical cohort of PLWH aged 18 and above receiving care at eight sites between January 2010 and March 2018. Participants: 16 505 PLWH were included in this study. Main outcome measures: Anaemia risk and haemoglobin change were estimated among PLWH for person-time on a protease inhibitor (PI) or an integrase strand transfer inhibitor (INSTI)-based regimen, relative to a non-nucleoside reverse transcriptase inhibitor (NNRTI)-based reference. We also examined PLWH on regimens containing multiple core classes. Cox proportional hazards regression analyses were conducted to measure the associations between time-updated ART classes and incident anaemia or severe anaemia. Linear mixed effects models were used to examine the relationships between ART classes and haemoglobin change. Results: During a median of 4.9 years of follow-up, 1040 developed anaemia and 488 developed severe anaemia. Compared with NNRTI use, INSTI-based regimens were associated with an increased risk of anaemia (adjusted HR (aHR) 1.26, 95% CI 1.00 to 1.58) and severe anaemia (aHR 1.51, 95% CI 1.07 to 2.11) and a decrease in haemoglobin level. Time on multiple core classes was also associated with increased anaemia risk (aHR 1.39, 95% CI 1.13 to 1.70), while no associations were found for PI use. Conclusion: These findings suggest INSTI use may increase the risk of anaemia. If confirmed, screening for anaemia development in users of INSTIs may be beneficial. Further research into the underlying mechanisms is warranted.